Aspergillus capibaribensis (Eurotiales, Trichocomaceae), a new species in section Cremei - Felipe, Maria Tamara C.; Barbosa, Renan N.; Bezerra, Jadson D.p.; Magalhães, Oliane M.c.; Paiva, Laura M.; Souza-Motta, Cristina M. (Phytotaxa, 2024)
In this study we describe a new species of Aspergillus in section Cremei deposited in the URM culture collection (Micoteca URM Profa. Maria Auxiliadora Cavalcanti) of the Departamento de Micologia, Universidade Federal de Pernambuco (Recife, Pernambuco, Brazil). Another strain was obtained from samples taken from pollen pots inside nests of Melipona scutellaris (stingless bee). Morphological and phylogenetic evidence based on sequencing of ITS rDNA, BenA, CaM and rpb2 markers supported the description of taxonomic novelty. Aspergillus capibaribensis sp. nov. is morphologically similar and phylogenetically close to A. flaschentraegeri - the distinctive features are uniseriate and hyaline conidiophores, short and smooth conidia and smaller vesicles compared to the micromorphological structures of A. flaschentraegeri. This record also expanded the knowledge of species in Aspergillus section Cremei in a tropical country such as Brazil.